Upgraded stability analysis of milling operations by means of advanced modeling of tooling system bending. (February 2017) - Totis, G.; Albertelli, P.; Torta, M.; Sortino, M.; Monno, M.
Abstract: The problem of undesired self-excited chatter vibrations in milling is very common. However, only in the last two decades some significant achievements for the theoretical understanding of this intricate phenomenon have been accomplished. Nevertheless, state of the art dynamic models are still not able to completely explain milling dynamics and chatter onset during some conventional milling operations performed by conventional cutting tools. In this research work, a revolutionary model of tooling system dynamics and of the regenerative effect in milling will be presented. The new model introduces a significant correction to the predicted stability borders when the cutter diameter is relatively large in comparison with tooling system overhang and when curved or inclined cutting edges are applied. Accordingly, the new approach may be of great interest for many industrial applications. The model has been successfully validated by performing experimental modal analysis, cutting force coefficient identification and stability lobes diagram determination, through many specific cutting tests. In the considered case study, where the afore mentioned geometrical features of the tooling system were still moderate, a significant shift of the stability borders of about +25% was experimentally observed and correctly predicted by the new approach. Abstract : Graphical abstract: Abstract : Highlights: Improved, generalized model of milling dynamics and regenerative effect is proposed. Additional degrees of freedom and force momenta included. Increased accuracy of the predicted stability lobes. Significant improvements for large diameter cutters with inclined cutting edges. Successful experimental validation.